2017
DOI: 10.1016/j.amc.2017.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Two-walks degree assortativity in graphs and networks

Abstract: Abstract. Degree ssortativity is the tendency for nodes of high degree (resp. low degree) in a graph to be connected to high degree nodes (resp. to low degree ones). It is usually quantified by the Pearson correlation coefficient of the degree-degree correlation. Here we extend this concept to account for the effect of second neighbours to a given node in a graph. That is, we consider the two-walks degree of a node as the sum of all the degrees of its adjacent nodes. The two-walks degree assortativity of a gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 57 publications
(31 reference statements)
1
14
0
5
Order By: Relevance
“…The average lth neighbor degree k l (k) is the average degree of nodes separated by l from a node of degree k. They found that social networks exhibit disassortative degree correlations on long-range scales, while nonsocial networks do not indicate such a tendency. The two-walks degree assortativity proposed by Allen-Perkins et al [50] is another type of assortativity measure be-yond nearest neighbors. This quantity is defined as the Pearson correlation coefficient of the sum of the nearestneighbor degrees of adjacent nodes, which reflects second neighbor degree correlations.…”
Section: Introductionmentioning
confidence: 99%
“…The average lth neighbor degree k l (k) is the average degree of nodes separated by l from a node of degree k. They found that social networks exhibit disassortative degree correlations on long-range scales, while nonsocial networks do not indicate such a tendency. The two-walks degree assortativity proposed by Allen-Perkins et al [50] is another type of assortativity measure be-yond nearest neighbors. This quantity is defined as the Pearson correlation coefficient of the sum of the nearestneighbor degrees of adjacent nodes, which reflects second neighbor degree correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Since the only direct neighborhood (or egonetwork) of nodes can not be taken into consideration due to its limited expressive power (inherited in the scale-free-like degree distribution of complex networks), the issue is to define connectivity boundednesses able to circumscribe those nodes whose importance is fundamental in the assortative attitude measurement of a target one. While some lines of research focused on degree assortativity [13] (extended to cope with higher-order notions of node neighborhood such as a two-walks degree correlation [14] or transsortativity [15]), the node-attributed counterpart of the problem has not received much of attention.…”
Section: Relatedmentioning
confidence: 99%
“….102 6.1. Asortatividad de grado, r k , y asortatividad de dos-pasos, rk, calculadas para las redes del modelo de [APGP16], empleando la metodología de [APPE17], cuando el sistema se halla en un régimen estacionario estadístico. Los datos se han obtenido al simular el sistema durante t = 5000 unidades de macro-tiempo, con C = 3. .…”
Section: Time Evolution Of Tanunclassified
“…A continuación se reproducen algunos de sus principales hallazgos, ya que éstos constituyen el punto de partida de [APPE17], presentado en el capítulo 4.…”
Section: Mezcla Asortativa Según El Grado Y Estructura De Una Redunclassified
See 1 more Smart Citation